BAMBU: ALTERNATIF BAHAN BANGUNAN DI DAERAH RAWAN GEMPA - Sukawi, Sukawi (TERAS)
Along time, bamboo has been known by society as a building material. Bamboo, a natural wealth of Indonesian society actually has the advantages are very suitable as an alternative for problem solving to housing in earthquake areas. For Indonesia as a seismic area and the climate is tropical, bamboo has the advantages when used as residential building materials. Bamboo has a high enough power, ever the skin for several species of bamboo has tensile strength then steel. Besides durability, bamboo has a very long level if the true preservation process. When an earthquake occurred, houses are in the fruit of the bamboo will not immediately collapse because it is elastic and lightweight, other than it can give more time for occupants to immediately save himself. The use of bamboo as structural materials building earthquake resistant housing is still the right solution in terms of economy, convenience and adjustments to the force caused by the earthquake compared to the other roof structure material.